Pan American Exposition March and Two Step - E.B. Ralph::::::::: (Denton Cottier & Daniels)
On cover: Dedicated to Fred C.M. Lautz, Buffalo, N.Y. Also on cover is photograph, printed in blue, of the sculpture Gay music from the Temple of Music, c1901 by the Pan-American Exposition Co. Score c1898 by E.B. Ralph.